“The Workshop for the Nation’s Soul” vs. “A Rabbi Factory”—Contrasting the Lithuanian Yeshiva with the Rabbinical Seminary - Asaf Yedidya (Religions)
The central institutional model that served Jewish Orthodoxy in its struggle with the threat to the tradition of the modern era and from which grew its intellectual leadership was ultimately the model of the Lithuanian Yeshiva. However, from the second half of the nineteenth-century, new models of Jewish higher education institutions emerged and were even adopted by Orthodox circles. How, then, did the trustees of the Lithuanian yeshiva model see the new institutional models? Our discussion will focus on the modern yeshivas and rabbinical seminaries that accepted the Orthodox halakhic view, including the Tahkemoni rabbinical seminary in Warsaw, the Hildesheimer Seminary in Berlin (1873–1938), and the Seminary for the Diaspora in Jerusalem (1956). The Lithuanian rabbis held to the supremacy of the Lithuanian Yeshiva model. However, until World War II, they saw the Orthodox rabbinical seminary as an institute suitable to its time and place—Germany, most of whose Jews were liberal—and did not consider it able to produce a Torah scholar worthy of his name. They opposed the establishment of rabbinical seminaries in Eastern Europe and the Land of Israel, and after the war, when the issue of establishing a rabbinical seminary in Jerusalem was raised, they rejected the Orthodox rabbinical seminary outright and no longer recognized its contribution to its time and place—Germany.